Dynamic resistance capacity of GPC slab under pendulum impact loading - Chen, Chong; Zhang, Xihong; Hao, Hong (Elsevier, 2023)
Geopolymer concrete (GPC) as a green construction material has the potential to substitute traditional concrete, but there is a lack of understanding of the performances of geopolymer concrete structures subjected to dynamic loadings. This study investigates the dynamic responses of reinforced concrete slabs made of ambient cured alkali-activated GPC under static and dynamic concentrated load. Laboratory tests are performed which revealed that GPC slabs exhibited typical punching shear failure model under both static and impact load. Current design codes including ACI, Eurocode 2 and CSCT model can well predict the static punching resistance capacity of GPC slab, but fail to predict the dynamic punching resistance. Numerical modelling is carried out to investigate the dynamic punching shear mechanism. The results indicate that the impact response of GPC slab is highly influenced by inertial effect. In the initial response stage the impact force is mainly resisted by the slab inertial resistance. The GPC dynamic material properties and structural dynamic amplification effect affect the dynamic response and damage of GPC slabs. Intensive numerical simulations are performed to quantify the influences of slab thickness, reinforcement ratio, impactor weight and impact velocity on impact responses of GPC slabs. Empirical formula is derived based on the test and numerical results to predict the dynamic punching resistance of reinforced GPC slabs.